Functional feeding groups of mayfly nymphs (Ephemeroptera) in South African rivers of the North West and Limpopo Provinces - Bossman, Esi H. (University of the Witwatersrand, Johannesburg, 2024)
Researchers, primarily in the Northern hemisphere, have extensively studied mouthpart morphology and dietary variability in Ephemeroptera (colloquially called mayflies). Ephemeroptera are key primary consumers in rivers around the world and are used as aquatic biomonitoring indicators due to interspecific variation in ecological tolerances that make them good indicator taxa. Cummins (1973, 1974) created a functional feeding groups (FFG) classification system, based on northern hemisphere macroinvertebrates, as a universal tool to functionally categorise organisms based on their primary feeding mode within their habitat. The FFG classification system is useful in identifying interrelations between structural and functional components of an ecosystem. The aim of this study was to contribute knowledge on FFGs for particular mayfly species, in the southern African savanna biome, through mouthpart morphology and gut content analysis. Four study sites were sampled from the Magaliesberg (M) and Waterberg (W) catchments. There were three species studied, namely Afroptilum parvum (Family Baetidae), Afronurus barnardi (Family Heptageniidae) and Elassoneuria sp. (Family Oligoneuriidae). These species’ mouthparts were dissected and their macro- and microstructures were prepared for viewing with Scanning Electron Microscopy (SEM) and light microscopy. Micrographs and images showed variation in mouthpart morphology between all three species, with special attention to the labia and maxilla microstructures. The identification and description of microstructures that differentiate mayfly species (and the adaptations of these appendages to facilitate food uptake and ingestion) are important to address knowledge gaps regarding mayfly mouthpart morphology. A Principal Component Analysis (PCA) showed distinct grouping of the three species, with mandibles and maxillary palps showing the most variation between species. After analysis, the following feeding groups were assigned: Afroptilum parvum is a collector-gatherer feeder, Afronurus barnardi is a brusher-scraper feeder and Elassoneuria sp. is a filter feeder. This study showed, in part, that the Cummins’ (1973, 1974) classification categories were too broad for classifying organisms from a South African savanna stream. However, it is a good foundational starting point for region specific FFG classification systems. Thus, it is recommended to use the classification system Cummins created as a starting point for classifying organisms into FFGs with an initial definition that can be expanded upon to create individual classification systems for different localities.
A dissertation submitted in fulfilment of the requirements for the Degree of Master of Science in the School of Animal, Plant and Environmental Sciences Faculty of Science University of the Witwatersrand, Johannesburg, 2024
Keywords: Ephemeroptera; Functional Feeding Groups; Afroptilum parvum; Afronurus barnardi; Elassoneuria sp; Magaliesberg; Waterberg; SDG-15: Life on land